Discrimination in modern global society: on the example of age criterion - Zharovska, Iryna; Kovalchuk, Vitaliy (ScienceRise: Juridical Science, 2020)
The article considers the problems of discrimination of persons on the basis of age criteria. Particular attention is paid to the problem of discrimination against the elderly. It is stated, that aging is a global problem due to its dual nature. On the one hand, we can say about the trend of increasing life expectancy, which is a consequence of the development of science, medicine and biotechnology, on the other hand, the cause of aging is the low birth rate, which falls annually. One of the legal manifestations of the population aging is increasing discrimination. Health status, type and level of activity, labor productivity and other socio-economic characteristics of the elderly change significantly. New measures and concepts of population aging have significant consequences for assessing the standard of living and living conditions of this category of people, their productive rate and other contribution to society and their needs for social protection and health care. Age discrimination is positioned as one of the manifestations of prejudice, associated with the so-called ageism, the spread of presumed group features, related to age, to persons belonging to the appropriate age group, regardless of their individual characteristics. It has been proven, that despite the significant positive axiological aspects of public health care, the interplanetary trend of an aging nation carries global challenges, including social and economic challenges, tax, communication, psychological and legal. Age equality ensures equal participation in society for people of all ages and is an important factor in the legal policy of democracy states. The problem of age discrimination is complex, discrimination in old age is rare for reasons only of old age, more often it is based on multiple factors of social, economic, gender, labor criteria. The authors single out the types of age discrimination in the following areas: in the socio-economic sphere; labor discrimination; in the field of social activity and communication, gender and age discrimination